2018
DOI: 10.1038/s41598-018-28783-2
|View full text |Cite
|
Sign up to set email alerts
|

A V-to-F substitution in SK2 channels causes Ca2+ hypersensitivity and improves locomotion in a C. elegans ALS model

Abstract: Small-conductance Ca2+-activated K+ (SK) channels mediate medium afterhyperpolarization in the neurons and play a key role in the regulation of neuronal excitability. SK channels are potential drug targets for ataxia and Amyotrophic Lateral Sclerosis (ALS). SK channels are activated exclusively by the Ca2+-bound calmodulin. Previously, we identified an intrinsically disordered fragment that is essential for the mechanical coupling between Ca2+/calmodulin binding and channel opening. Here, we report that substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 48 publications
(81 reference statements)
0
24
0
Order By: Relevance
“…Using site-directed mutagenesis and electrophysiological recordings, we found that decreasing hydrophobicity by the F410A mutation led to the hyposensitivity of SK2 channels to Ca 2+ , whereas increasing hydrophobicity by V407F mutation caused hypersensitivity of SK2 channels to Ca 2+ . 35 Limited by the structural information available back then, we were only able to identify M411 as a residue that could interact with the ectopic phenylalanine in the hyperactive V407F mutant channels. With a cryo-EM structure of the human SK4 channel published in 2018 36 as the template, we generated a homology model of the rat SK2 channel ( Figure 1A and Figure S1) as described previously, 35 which allowed us to take a fresh look at the cognate V407 residue.…”
Section: Mutagenesis Of the Hydrophobic Residues In The S4-s5 Linkementioning
confidence: 94%
See 4 more Smart Citations
“…Using site-directed mutagenesis and electrophysiological recordings, we found that decreasing hydrophobicity by the F410A mutation led to the hyposensitivity of SK2 channels to Ca 2+ , whereas increasing hydrophobicity by V407F mutation caused hypersensitivity of SK2 channels to Ca 2+ . 35 Limited by the structural information available back then, we were only able to identify M411 as a residue that could interact with the ectopic phenylalanine in the hyperactive V407F mutant channels. With a cryo-EM structure of the human SK4 channel published in 2018 36 as the template, we generated a homology model of the rat SK2 channel ( Figure 1A and Figure S1) as described previously, 35 which allowed us to take a fresh look at the cognate V407 residue.…”
Section: Mutagenesis Of the Hydrophobic Residues In The S4-s5 Linkementioning
confidence: 94%
“…The homology model of the rat SK2 channel was described in our previously report. 35 The WT or N293A/V407F mutant SK2 channels were immersed in an explicit lipid bilayer of POPC, POPE, POPS and cholesterol with molecular ratio of 25:5:5:1, 40 and a water box in 168.1Åx165.6Åx140.0Å dimension by using the CHARMM-GUI Membrane Builder webserver (http://www.charm m-gui.org/?doc=input/ membrane). 150mM KCl and extra neutralizing counter ions were added into the systems.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 3 more Smart Citations